”Are those the only two solutions?̋”: dealing with choice, agency and religion in digital games - Knoll, Tobias (Online - Heidelberg journal of religions on the internet, 2015)
Choice and ‘agency’ are frequently named as key factors in describing videogames and their unique features in respect to other forms of media. Through a multitude of minor and major decisions (or illusions thereof), players are given the impression of being an integral part of the narrative and ludic experience of a game, oftentimes forcing them to face the consequences of their actions in the game world.This paper aims at providing some insights into academic and public discussions of ‘agency’ in the context of digital games and, drawing on the examples of Call of Duty: Black Ops, The Graveyard and Mass Effect 2. An argument is made for a further emphasis on the role of ‘agency’ within the field of religion and digital games as well as a more differentiated (yet still complementary) approach toward ‘player agency’ and ‘game agency’.